2015
DOI: 10.1021/acs.estlett.5b00061
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning, Aqueous Solubility, and Dipole Moment Data for cis- and trans-(4-Methylcyclohexyl)methanol, Principal Contaminants of the West Virginia Chemical Spill

Abstract: In 2014, the U.S. National Response Center recorded more than 30000 incidents of oil spills, chemical releases, or maritime security issues, including crude (4-methylcyclohexyl)­methanol (MCHM) that contaminated river and drinking water in West Virginia. This research yielded physicochemical partitioning data for the two major compounds released in West Virginia, cis- and trans-(4-methylcyclohexyl)­methanol. Octanol–water partition coefficients (K OW) were 225 for cis-4-MCHM and 291 for trans-4-MCHM. The aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 21 publications
5
32
2
Order By: Relevance
“…However, the abundances of the cis and trans isomers were approximately 33% and 57%, respectively, which are opposite to the relative abundances observed in MCHM. Similar differences in isomer ratios for MCHM and crude MCHM have been reported previously (Foreman et al, 2015; Dietrich et al, 2015). Thus, it is possible that the MCHM trans isomer drives the sensitization potential of crude MCHM.…”
Section: Discussionsupporting
confidence: 88%
“…However, the abundances of the cis and trans isomers were approximately 33% and 57%, respectively, which are opposite to the relative abundances observed in MCHM. Similar differences in isomer ratios for MCHM and crude MCHM have been reported previously (Foreman et al, 2015; Dietrich et al, 2015). Thus, it is possible that the MCHM trans isomer drives the sensitization potential of crude MCHM.…”
Section: Discussionsupporting
confidence: 88%
“…28,30 Follow-up work by others weeks after the spill revealed that publicly accessible EPA databases such as SPARC and EPIWEB either contained or could be used to estimate these properties. 19,42 Based on these databases many of the tank liquid ingredients were moderately to highly soluble in water (up to 28 000 ppm for some ingredients at 21°C), volatile (up to 118 mmHg at 21°C), and their fate was temperature dependent. Others confirmed through experiments months after the spill that 4-MCHM volatilized from wa-ter, 14,15 and the water solubility and log K ow for each 4-MCHM isomer was found to be similar (1010 ppm and 2.46 and 1300 ppm and 2.35 at 21°C for transand cis-isomers, respectively).…”
Section: Constituents In Tank 396 Liquid and Their Chemical Propertiesmentioning
confidence: 99%
“…The trans-isomer however was three times more volatile than the cis-isomer. 42,43 EPA databases could only estimate the properties of total 4-MCHM, not properties for each isomer.…”
Section: Constituents In Tank 396 Liquid and Their Chemical Propertiesmentioning
confidence: 99%
“…Applied fertilizers and pesticides can reach water sources either by surface run off or to groundwater by leaching through the soil. Heavy rain or extensive irrigation processes can further aggravate the leaching of contaminants to the groundwater [5]. Fertilizers and pesticides can cause serious health problems when constantly consumed by humans.…”
Section: Introductionmentioning
confidence: 99%